The effect of calcium supplementation during pregnancy on fetal and infant growth: a nested randomized controlled trial within WHO calcium supplementation trial. - Abdel-Aleem, H; Merialdi, M; Elsnosy, E; Elsedfy, G; Abdel-Aleem, M; Villar, J (2009)
OBJECTIVE: To evaluate whether prenatal calcium supplementation affects fetal and infant growth during the first year of life. METHODS: Ninety-one pregnant women and 159 mothers and their infants enrolled beginning before 20 weeks gestation, and women received daily supplements containing either 1.5 g calcium or placebo. Women were examined by ultrasound at 20, 24, 28, 32 and 36 weeks to evaluate fetal biometry. During the first year after delivery, sub-groups of infants born from mothers participating in the trial were examined to assess infant growth. Anthropometric measurements of the infants were assessed. Mothers were inquired about lactation patterns, morbidities of the infants, separation from the mother, and admission to hospital. RESULTS: Ultrasound measurements of fetal biometry did not show any differences between fetuses whose mothers received calcium supplementation during pregnancy and those who received placebo. Concerning infant growth, the mean weight and head circumference of infants born to calcium-supplemented mothers were similar to those born to placebo-supplemented mothers during the first year of life. The mean mid-arm circumference and mean length were significantly higher in the infants of the calcium group at sixth and ninth month, respectively. But, at 12 months, there were no significant differences in any of the anthropometric measurements. CONCLUSION: Calcium supplementation during pregnancy of women with low calcium intake does not have a noticeable impact on fetal and infant growth during the first year of life.